2019
DOI: 10.17798/bitlisfen.649129
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of the Total Efficiency for NaI(Tl) Detector by GATE Simulation

Abstract: In this study the total efficiency of the NaI(Tl) detector have been calculated by using Geant4 based GATE simulation program. The simulation was performed using point and disc isotropic gamma-ray sources at various distance between source and detector in the photon energy range 50-3000 keV. Results were compared with different analytical and Monte Carlo calculations obtained in the time of the periods 1958-2018. The calculated and simulated data indicated good agreement with finding more sensitive GATE simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…To demonstrate the effect of the source dimensions, the simulation was carried out for a radiant source with a disk shape. The results were compared with the published results of the international code Geant4 based GATE simulation program 29 , which clearly showed quite well congruence, see Fig. 9.…”
Section: Resultsmentioning
confidence: 63%
“…To demonstrate the effect of the source dimensions, the simulation was carried out for a radiant source with a disk shape. The results were compared with the published results of the international code Geant4 based GATE simulation program 29 , which clearly showed quite well congruence, see Fig. 9.…”
Section: Resultsmentioning
confidence: 63%
“…The results of the detector module under study were still much larger in error than the detectors from research using PMT with solar cell sensors and NaI (TI), [24], [28]. In this case, the drawback of the module that the author developed is that the problem with the detector itself which is less stable and linear.…”
Section: Discussionmentioning
confidence: 96%
“…In another study entitled PMT (Effect of High Voltage Variations in Solar Tubes) on the Output Amplitude of the NaI (T1) detector, a tool to measure photon radiation has been made using a two-channel analyzer (MCA). The results showed that there was a linear correlation between high voltage and amplitude changes, so reducing the high voltage interval will cause changes in amplitude [24]- [28]. A similar study entitled investigating factors affecting the quality assurance of x-ray surface radiation therapy machines was further done as well.…”
Section: Introductionmentioning
confidence: 99%